(NkOSMI^ESKIE LU^I I IZOTOPNAQ \KOLOGIQ (B:s ((NsBORNIK NAU^NYH TRUDOW(B) /s ((NlENINGRAD (B:s (Nb(B. (NI(B,s, 1988)
(NbIBLIOGR(B. (NW KONCE ST(B.s
Keywords: (NkOSMI^ESKIE LU^Is; (N|KOLOGI^ESKIE SISTEMY (B- (NiZOTOPNYJ METOD ISSLEDOWANIQs